PERAN GURU DALAM PENGELOLAAN KELAS - Minsih Minsih; Aninda Galih D (Profesi Pendidikan Dasar, 2018)
Abstract: The purpose of this study was to know the role of teachers in the management of learning in the classroom at MI Muhammadiyah PK Kartasura. The research was conducted through qualitative approach. Data were collected by interview, observation, and documentation. The research data was validated by triangulation technique. Data were analyzed through three stages: data reduction, data display, conclusions drawing / verification. This study concludes that the role of teachers in implementing the teaching and learning process is a key element in the management of learning. At MI Muhammadiyah PK Kartasura, teachers should plan, implement and evaluate learning and build good inter-relationships among all members of the learning process. Teachers must also act as facilitators, motivators, demonstrators, mediators and evaluators, in the management of innovative classes. One of the indicators of learning management in innovative classes at MIM PK Kartasura was student-centered learning.